Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1002/1097-0142(19860115)57:2<391::aid-cncr2820570235>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of tobacco and alcohol in cancer of the larynx, pharynx, and mouth

Abstract: Two thousand five hundred forty male patients with cancer of larynx, pharynx, and mouth were examined in the same hospital between 1975 and 1982. Different sites were compared according to alcohol and tobacco consumption: oropharynx, hypopharynx, larynx supraglottis, larynxglottis, epilarynx, lip, tongue-tip, and tongue lateral border, other tongue sites, gum, floor of the mouth, and buccal mucosa. For tobacco, the mean daily consumption of smokers and exsmokers did not differ according to location (except in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
99
0
10

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(119 citation statements)
references
References 10 publications
10
99
0
10
Order By: Relevance
“…[1][2][3][4][5]20 Both smoking and alcohol consumption have been shown to be independent risk factors for upper digestive tract cancers. When combined, there is evidence indicating that alcohol and tobacco act together in a multiplicative rather than in an additive manner, having synergistic tumour-promoting effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5]20 Both smoking and alcohol consumption have been shown to be independent risk factors for upper digestive tract cancers. When combined, there is evidence indicating that alcohol and tobacco act together in a multiplicative rather than in an additive manner, having synergistic tumour-promoting effects.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Many of the compounds in the tobacco smoke are carcinogenic, but, in contrast, the tumour-promoting effects of alcohol drinking has so far been less well defined. Acetaldehyde, the first metabolite of ethanol, has been shown to be carcinogenic in animals and there exists strong evidence of its carcinogenic action also in man.…”
Section: Abstract: Acetaldehyde; L-cysteine; Upper Digestive Tract; mentioning
confidence: 99%
“…Primary prevention via programmes to eliminate risk factors may become important (Warnakulasuriya and Johnson, 1996). Previous studies have demonstrated that smoking was highly associated with leukoplakia (Bouquot, 1987;Roed-Petersen, 1982;Brugere et al, 1986;Evstifeeva and Zaridze, 1992) but whether betel nut -containing arecoline, lime and piper (one kind of pepper) -was significantly related to leukoplakia has not been fully addressed. Since the consumption of betel nut in Taiwan has been increasing, elucidation of any association is becoming increasingly important.…”
mentioning
confidence: 99%
“…Since the consumption of betel nut in Taiwan has been increasing, elucidation of any association is becoming increasingly important. The association between alcohol consumption and leukoplakia is also inconclusive (Blot et al, 1988;Brugere et al, 1986;Evstifeeva and Zaridze, 1992).…”
mentioning
confidence: 99%
“…Acometem com mais freqüência o sexo masculino na 5ª e 6ª décadas de vida 8 , sendo em 80% atribuído a fatores ambientais, dietéticos, ocupacionais, infecção viral, fator imunológico e alterações genéticas 9,10 . Porém, o fator de risco dominante e comum a quase todos os portadores de câncer de orofaringe continua sendo o consumo de bebida alcoólica em associação ao tabaco 1,7,[11][12][13][14][15][16][17] .…”
Section: Introductionunclassified